Madrasah Independent Curriculum in the Era of Society 5.0 (Case Study of KMA RI Policy No. 347 of 2022 at MTs Muhammadiyah Al-Muhajirin Gunung Kidul) - Aulia, Nur Annisa; Sabarudin, Sabarudin (The Magister of Islamic Education IAIN Pontianak, 2025)
This research is a case study that aims to analyze the implementation of the Madrasah Merdeka Curriculum (KMM) at MTs Muhammadiyah Al-Muhajirin Gunung Kidul in the context of the policy of the Ministry of Religious Affairs of the Republic of Indonesia Number 347 of 2022 and the dynamics of the Society 5.0 era. The reason for raising this theme is the need for educational institutions, especially madrasah, to be able to adapt to educational transformations that emphasize strengthening character, digital skills, and response to social change. This study aims to describe the process of design, implementation, and evaluation of KMM carried out by MTs Muhammadiyah Al-Muhajirin, as well as the extent to which these practices are aligned with applicable national policies. The research method uses a qualitative approach with data collection techniques through participant observation, in-depth interviews with key informants, and analysis of official documents related to KMA RI guidelines No. 347 of 2022. The results showed that the implementation of KMM at MTs Muhammadiyah Al-Muhajirin has reflected most of the principles and guidelines of KMA RI No. 347 of 2022 in daily learning activities, although there are still challenges in terms of technology integration and overall strengthening of student character, and the implementation of KMM has a positive impact on the development of student competencies, especially in critical thinking skills, collaboration, and technology utilization in accordance with the demands of the Society 5.0 era. These findings have significance as a strategic reference for other madrasahs in developing and implementing curriculum policies that are adaptive and contextual to the times.